Neue Beobachtungen zum Geschichtswerk des Iulius Florus als eines spätaugusteischen Autors - Koch, Holger (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Baldwin (1988) summarized the main problems of Florus 25 years ago. These are still unsolved. They deal with the identification of the Flori, the date of Florus’ history and the correct title of the work. The most vexing of all the questions associated with the history is its date: Trajan (98-117 A.D.), Hadrian (117-138 A.D.) or Antoninus Pius (138-161 A.D.). An Augustan date has been plausibly proposed by Neuhausen (1992 and 1994) against the „communis opinio”. Following his studies I can explain and solve all the „anachronisms”, which were caused by the false dating of Florus to the second century A.D. According to Neuhausen’s and my own studies Florus’ history must therefore be dated after the consecration of Augustus (17th of September, 14 A.D.) [~ first edition]; the second edition came from the time of Trajan, because the preface contains two short interpolations with the name of this emperor at its end. The writer of the history has to be identified with Iulius Florus, the famous addressee of Horace’s two epistles. The original work probably has only one volume. The title Epitoma de Tito Livio bellorum libri duo is wrong and has to be changed into Rerum gestarum populi Romani breviarium or tabella.